Na puti k utverzhdeniyu: Imeni v nauke ili nauki v sporte? - Stepanov, V. V. (Teorija i Praktika fiziceskoj Kul'tury, 1998)
The paper is devoted to the problems of sports training in connection with the discussion caused by the professor Yu. V. Verkhoshansky`s article published in the second issue of this journal in 1998. The author represents the retrospective analysis of the notion`s evolution on the problem of a sports training`s periodization, beginning from the middle of the XIX-th century. He criticizes the style of the present discussion as well as all the preceding ones. The own conception of the sports training controlling on the basis of the correction system, basing on the 3-points system of the athlete`s self assessments and the data of scientific recommendations is offered by the author.